2018
DOI: 10.4103/ua.ua_98_17
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic evaluation of children with urolithiasis

Abstract: Aim:The aim of the study is to identify the prevalence of metabolic abnormalities in children with urolithiasis.Materials and Methods:This is a prospective study; all children below 15 years who are found to have urolithiasis were prospectively evaluated with relevant history, clinical examination, and urine and serum testing. Metabolic workup includes complete urine examination, urine culture and sensitivity, and 24-h urinary analysis (lithorisk profile).Results:A total of 55 patients are included in the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 38 publications
1
9
0
1
Order By: Relevance
“…In our study, the most common presenting feature was UTI, followed by flank or abdominal pain and hematuria. These results are consistent with those of other studies [13,28,29]. Both visible and non-visible hematuria were relatively uncommon in our study compared with other reports [15,19].…”
Section: Discussionsupporting
confidence: 94%
“…In our study, the most common presenting feature was UTI, followed by flank or abdominal pain and hematuria. These results are consistent with those of other studies [13,28,29]. Both visible and non-visible hematuria were relatively uncommon in our study compared with other reports [15,19].…”
Section: Discussionsupporting
confidence: 94%
“…(Imamverdiev and Guseinzade, 2015). Studies have shown that hot conditions, reduced dietary fiber intake, and high intake of animal protein are important risk factors for urolithiasis (Gouru et al, 2018). There is a direct link between diet and urolithiasis, and studies have found that excessive intake of high-fat foods has a catalytic effect on the formation of urolithiasis (Shimizu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Hypercalciuria (> 300 mg/day) is defined as an increase in urinary calcium excretion, independent on serum calcium levels 38 . While, 99% of the body's calcium stores is found in the skeleton, only 1% remains in the intra and extracellular spaces 39 .…”
Section: Hypercalciuriamentioning
confidence: 99%